Efficient tetracycline hydrochloride removal by encapsulated phosphotungstic acid (PTA) in MIL–53 (Fe): Optimizing the content of PTA and recycling study. Issue 1 (February 2020) - Masoumi, Sara; Farshchi Tabrizi, Farshad; Sardarian, Ali Reza
Graphical abstract: Highlights: MIL–53 (Fe), PTA/MIL-53 (Fe) and PTA@MIL–53 (Fe) were used for TC.HCl removal. Encapsulated PTA in MIL–53 (Fe) had better performance than impregnated one. The optimum content of PTA encapsulated in MIL–53 (Fe) was 10 wt% for TC.HCl removal. The maximum adsorption capacity of PTA (10 wt%)@MIL–53 (Fe) was 1250 mg/g. The good reusability of PTA (10 wt%)@MIL–53 (Fe) made it a promising adsorbent. Abstract: The performance of tetracycline hydrochloride (TC.HCl) adsorption by MIL–53 (Fe), PTA/MIL–53 (Fe) (phosphotungstic acid impregnating via post modification) and four different contents of PTA in PTA@MIL–53 (Fe) (phosphotungstic acid encapsulating via one–pot method) were investigated. The results proved that the comparison adsorption capacity of the adsorbent in high concentration of TC.HCl is: PTA(10 wt%)@MIL–53 (Fe) > PTA(16 wt%)@MIL–53 (Fe) > PTA(6 wt%)@MIL–53 (Fe) > PTA(30 wt%)@MIL–53 (Fe) > PTA/MIL–53 (Fe) > MIL–53 (Fe). The maximum adsorption capacity of TC.HCl on to PTA(10 wt%)@MIL–53 (Fe) using Langmuir equation was 1250 mg/g which is extremely high. The isotherm adsorption data were found to fit Langmuir model and the adsorption process was matched by pseudo–second–order kinetics model. The thermodynamic assessments expressed that the process is spontaneous and endothermic. The regeneration experiments by 0.1 M HCl/ethanol (10/90, v/v) as elution agent showed that the adsorption capacity was not changed significantly even after 3 times reusing. PTA (10 wt%)@MIL–53 (Fe) showed a great potential to be a good adsorbent for TC.HCl removal from an aqueous media and also capable of being regenerated.